Suasana Toko, Suasana Hati, Kualitas Pelayanan, dan Keputusan Pembelian Antara Konsumen Restoran Modern dan Restoran Tradisional - Risna Sutiama; Pitri Yandri (Indonesian Journal of Economics Application (IJEA), 2019)
The study aims to compare the perceptions of consumers of modern restaurants and traditional restaurants about the store atmosphere, mood, and service quality and analyze their influence on consumer purchasing decisions in both modern restaurants and traditional restaurants. The research method used in this study is quantitative research design with comparative and associative analysis. Data collection techniques were conducted by survey with questionnaire instruments with a sample of 40 respondents in each restaurant. The analysis technique used Chi Square Test and Factor Analysis. The results of this study indicate that there are differences in perceptions between consumers of modern restaurants and traditional restaurants about variable store atmosphere, mood and service quality in modern restaurants and traditional restaurants.